Long-term effect of rifampicin-based Anti-TB regimen coadministration on the pharmacokinetic parameters of efavirenz and 8-Hydroxy-Efavirenz in ethiopian patients - Habtewold, Abiy; Burhenne, Jürgen (Journal of clinical pharmacology, 2016)
We compared the pharmacokinetic (PK) exposure parameters of efavirenz (EFV) and its major inactive metabolite, 8-hydroxy-efavirenz (8-OH-EFV), in an open-label, single-sequence, and parallel design of HIV-infected and tuberculosis (TB)-HIV-coinfected Ethiopian patients in the HIV-TB Pharmagene study with 20 and 33 patients, respectively. Both treatment groups underwent PK sampling following oral 600 mg EFV in week 16 of initiating EFV-based combination antiretroviral therapy. The TB-HIV-coinfected group repeated the PK sampling 8 weeks after stopping rifampin (RIF)-based anti-TB treatment. Between-treatment group analysis indicated no significant effect of RIF-based anti-TB cotreatment on PK exposure parameters of EFV, nor was there a significant effect after controlling for sex or CYP2B6 genotype. However, RIF-based therapy in TB-HIV-coinfected patients had significantly increased 8-OH-EFV PK exposure measures and metabolic ratio relative to HIV-only patients, AUC0-24 greater by 79%. The effect was more prominent in women and CYP2B6*6 carriers in within-sex and CYP2B6 genotype comparisons. Within-subject comparisons for AUC0-24 and Cmax when “on” and “off” RIF-based anti-TB cotreatment showed geometric mean ratios (90% confidence intervals) of 100.5% (98.7%-102.3%) and 100.2% (98.1%-102.4%), respectively, for EFV and 98.6% (95.5%-101.7%-) and 97.6% (92.2%-103.0%), respectively, for 8-OH-EFV. We report no significant influence of RIF-based anti-TB cotherapy on the EFV PK exposure measures. The study also calls for caution related to higher exposure to 8-OH-EFV during simultaneous coadministration of EFV and RIF-based anti-TB regimens, which may be associated with neurotoxicity, particularly in female patients and CYP2B6*6 carriers.